1996
DOI: 10.1021/bi960240k
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a Low-Barrier Hydrogen Bond in the Tryptophan Synthase Catalytic Mechanism

Abstract: In the absence of other substrates, L-Ser reacts rapidly with the tryptophan synthase alpha 2 beta 2 bienzyme from Salmonella typhimurium at pH 7.8 and 25 degrees C to give an equilibrating mixture of species dominated by comparable amounts of the L-Ser external aldimine Schiff base, E(Aex1), and the alpha-aminoacrylate Schiff base, E(A-A). The D-isomer of Ser is unreactive toward alpha 2 beta 2, and therefore, D,L-Ser can be used in place of L-Ser for investigations of catalytic mechanism. Due to the equilibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
28
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 46 publications
7
28
0
Order By: Relevance
“…This is in agreement with the very high 1 H chemical shifts measured by NMR for protons proposed to be involved in LBHB formation (5)(6)(7)(8)(9)(10)(11)(12). The emerging picture of LBHBs as having covalent bonds between charged atoms is thus in good agreement with this special spectroscopic characteristic of the LBHB systems.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…This is in agreement with the very high 1 H chemical shifts measured by NMR for protons proposed to be involved in LBHB formation (5)(6)(7)(8)(9)(10)(11)(12). The emerging picture of LBHBs as having covalent bonds between charged atoms is thus in good agreement with this special spectroscopic characteristic of the LBHB systems.…”
Section: Resultssupporting
confidence: 87%
“…It has been suggested that formation of ''short-strong'' hydrogen bonds (SSHB) or ''low-barrier'' hydrogen bonds (LBHB) can stabilize intermediates and͞or transition states of enzymatic reactions (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Originally, the involvement of LBHB in enzymatic reactions was suggested by Cleland (1) based on the observation of unusually low hydrogen fractionation factors for certain enzymes.…”
mentioning
confidence: 99%
“…The presence of the hydrogen bond between His 86 and Lys 87 in E-AA (19) is consistent with evidence from spectroscopic experiments that the abstracted ␣-proton of L-Ser is sequestered in a solvent-excluded site and possibly stored in a low barrier hydrogen bond (20 , and the phosphate of PLP. Indeed, the 31 P nuclear magnetic resonance chemical shift of the phosphate of the PLP, which is bound to the tryptophan synthase ␣ 2 ␤ 2 complex and ␤ 2 subunit from E. coli, is pH-independent from pH 6.5 to 8.6, whereas the PLP 31 P chemical shift of a model PLP derivative exhibits a pK a value of 6.23 (21).…”
supporting
confidence: 80%
“…Many researches are devoted to very strong hydrogen bonds, because of their important role as a transition state in biochemical reactions and enzyme catalysis [6][7][8][9][10][11][12]. Their unusual stabilization energy makes them to be distinguished from ordinary hydrogen bonds.…”
Section: Introductionmentioning
confidence: 99%